The validation analysis of the INSHORE system: a precise and efficient coastal survey system - Baptista, P. (2011)
Government and environmental entities are becoming increasingly concerned with qualifying and quantifying the erosion effects that are observed in sandy shores. Correspondingly, survey methodologies that gather data for such erosion studies are increasingly being demanded. The responsible entities are continually broadening their areas of interest, are concerned in the establishment of regular monitoring programmes and are demanding high accuracy from the geo-spatial data that is collected. The budget available for such monitoring activities, however, does not parallel the trend in the increasing demand for quality specifications. Survey methodologies need improvement to meet these requirements. We have developed a new land-based survey system-the INSHORE system-that is ideal for low cost, highly efficient and highly precise coastal surveys. The INSHORE system uses hi-tech hardware that is based on high-grade global positioning system (GPS) receivers and a laser distance sensor combined with advanced software algorithms. This system enables the determination of the ground coordinates of the surveyed areas with a precision of 1 to 2 cm, without having a sensor in contact with the ground surface. The absence of physical contact with the ground makes this system suitable for high-efficiency surveys. The accuracy of the positioning, which is based on advanced differential GPS processing, is enhanced by considering the estimated attitude of the GPS receiver holding structure and eliminates undesirable offsets. This paper describes the INSHORE survey system and presents the results of validation tests that were performed in a sandy shore environment.